Preparation and biological properties of ring-substituted naphthalene-1-carboxanilides - Gonec, Tomas; Kos, Jiri; Nevin, Eoghan; Govender, Rodney; Pesko, Matus; Tengler, Jan; Kushkevych, Ivan; Stastna, Vendula; Oravec, Michal; Kollar, Peter; O'Mahony, Jim; Kralova, Katarina; et al. (Molecules, 2014)
In this study, a series of twenty-two ring-substituted naphthalene-1-carboxanilides were prepared and characterized. Primary in vitro screening of the synthesized carboxanilides was performed against Mycobacterium avium subsp. paratuberculosis. N-(2-Methoxyphenyl)naphthalene-1-carboxamide, N-(3-methoxy-phenyl)naphthalene-1-carboxamide, N-(3-methylphenyl)naphthalene-1-carboxamide, N-(4-methylphenyl)naphthalene-1-carboxamide and N-(3-fluorophenyl)naphthalene-1-carboxamide showed against M. avium subsp. paratuberculosis two-fold higher activity than rifampicin and three-fold higher activity than ciprofloxacin. The most effective antimycobacterial compounds demonstrated insignificant toxicity against the human monocytic leukemia THP-1 cell line. The testing of biological activity of the compounds was completed with the study of photosynthetic electron transport (PET) inhibition in isolated spinach (Spinacia oleracea L.) chloroplasts. The PET-inhibiting activity expressed by IC50 value of the most active compound N-[4-(trifluoromethyl)phenyl]naphthalene-1-carboxamide was 59 μmol/L. The structure-activity relationships are discussed.
Keywords: antibakteriální látky; Naphthalenes; Hydrophobic and Hydrophilic Interactions; Electron Transport; vztahy mezi strukturou a aktivitou; Spinacia oleracea; chloroplasty; Anti-Bacterial Agents; anilidy; Microbial Sensitivity Tests; Anilides; naftaleny; Mycobacterium avium; mikrobiální testy citlivosti; Chloroplasts; fotosyntéza; hydrofobní a hydrofilní interakce; Photosynthesis; transport elektronů; Structure-Activity Relationship